Financing infrastructure in Asia and the Pacific capturing impacts and new sources - Yoshino,Naoyuki; Helble, Matthias; Abidhadjaev,Umid
"According to the book infrastructure investment is synonymous with economic development. Insufficient roads, railways, and utility systems reduce the quality of life for billions of people. This make firms less competitive. The demand for quality infrastructure is clear, but a significant gap exists between current financing schemes and the funding needs of recipient countries in Asia and the Pacific. This book examines the modalities for financing infrastructure projects in Asia and the Pacific, including (i) mapping out the benefits and needs of infrastructure investment, (ii) evaluating public and private sources of finance, (iii) evaluating potential new sources of finance, and (iv) recommending policies to promote public-private partnerships and attracting new private financing sources.."--Extracted from website